A cross‐sectional survey of moral distress and ethical climate – Situations in paediatric oncology care that involve children's voices. Issue 4 (20th April 2022) - Ventovaara, Päivi; af Sandeberg, Margareta; Petersen, Gitte; Blomgren, Klas; Pergert, Pernilla
Abstract: Aim: To assess experiences of morally distressing situations and perceptions of ethical climate in paediatric oncology care, with a focus on situations that involve children's voices. Design: Cross‐sectional survey. Methods: Registered Nurses at all four paediatric oncology centres in Denmark were asked to complete a web‐based questionnaire with Danish translations of the Swedish Moral Distress Scale‐Revised (MDS‐R) and the Swedish Hospital Ethical Climate Survey‐Shortened (HECS‐S). Data analysis included descriptive statistics and non‐parametric correlation tests. Results: Nurses ( n = 65) perceived morally distressing situations as rather uncommon, except for those that involved shortage of time, poor continuity of care and unsafe staffing levels. Most nurses (83%) found it disturbing to perform procedures on school‐aged children against their will, and 20% reported that they do this often. Perceptions of ethical climate were positive and healthcare professionals were perceived to be attentive to children's wishes.